The paradox of assessment in vocational education and training: learning outcomes and structural tensions - Nieto Ortiz, Jorge (Avances en Supervisión Educativa, 2026)
This paper analyses the tensions between the normative design of the Vocational Education and Training (VET) system in Spain and certain consolidated assessment practices, particularly the use of arithmetic compensation in the passing of vocational modules. Adopting a qualitative, legal-argumentative approach, the study examines the role of learning outcomes as units for the verification of competence with a certifying value, as well as their relationship with assessment criteria and evaluative decision-making. The analysis identifies what is referred to as the “certification paradox”: the coexistence of a regulatory model based on rigorous certifiable units with assessment practices that allow their completion without the effective acquisition of all the defined learning outcomes. Drawing on normative analysis and illustrative examples from professional contexts, the paper concludes that the uncritical application of compensatory mechanisms may undermine system coherence, legal certainty, and social trust in VET qualifications. This is of special interest for the educational inspectorate in the exercise of its educational advisory functions.